2021
DOI: 10.3390/nu13020394
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Oleoylethanolamide Treatment Decreases Hepatic Triacylglycerol Level in Rat Liver by a PPARγ/SREBP-Mediated Suppression of Fatty Acid and Triacylglycerol Synthesis

Abstract: Oleoylethanolamide (OEA) is a naturally occurring bioactive lipid belonging to the family of N-acylethanolamides. A variety of beneficial effects have been attributed to OEA, although the greater interest is due to its potential role in the treatment of obesity, fatty liver, and eating-related disorders. To better clarify the mechanism of the antiadipogenic effect of OEA in the liver, using a lipidomic study performed by 1H-NMR, LC-MS/MS and thin-layer chromatography analyses we evaluated the whole lipid compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 75 publications
(113 reference statements)
3
13
0
Order By: Relevance
“…Oxidative stress can modulate metabolic pathways by activating transcription factors, among which Nrf1 and Nrf2 play a key role [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. We measured the protein expression of Nrf1, Nrf2, and PPARγ, this latter being an Nrf2-downstream transcriptional factor [ 56 ], involved in the regulation of lipid metabolism [ 34 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative stress can modulate metabolic pathways by activating transcription factors, among which Nrf1 and Nrf2 play a key role [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. We measured the protein expression of Nrf1, Nrf2, and PPARγ, this latter being an Nrf2-downstream transcriptional factor [ 56 ], involved in the regulation of lipid metabolism [ 34 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…PPARγ is a regulator of lipid metabolism in hepatocytes; changes in the expression of this protein have been associated with non-alcoholic fatty liver diseases through the induction of lipogenic factors [ 57 ]. Recently, we demonstrated a PPARγ-mediated effect of OEA on reducing hepatic lipid accumulation in control rats [ 34 ]. Here, we found that HFD increased PPARγ expression ( Figure 3 D), and induced liver steatosis, both restored by OEA administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [ 45 ] demonstrated that the protein expression and activity of ACC, FAS, and SCD-1 were suppressed when the aberrant expression of SREBP-1 was suppressed. Furthermore, Romano et al [ 46 ] demonstrated that downregulation of SREBP-1 and PPAR-γ suppressed lipogenesis-specific gene expression. Whether the expression of these major lipogenic factors is regulated is one of the main indicators to determine the inhibitory effect of pharmacologically active substances on lipogenesis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPARs are important transcriptional factors in modulating liver inflammation [67], lipid metabolism [68], and cancer growth [69]. All three PPAR subtypes, including PPARα [70], PPARβ/δ [71], and PPARγ [72], play important roles in lipid metabolism, either in the liver or adipose tissues. For example, hepatocyte-specific PPARα deficiency mice showed a significant increase in oleic acid and linoleic acid compared with wild-type mice in fasting, partly due to a fasting-induced increase in fibroblast growth factor 21 (FGF21) expression [73].…”
Section: Pparsmentioning
confidence: 99%